2021
DOI: 10.1177/21582440211010721
|View full text |Cite
|
Sign up to set email alerts
|

To Be Resourced or to Become a Resource: Understanding Novice University Teachers’ Resource-Mediated Identity Construction

Abstract: This article reports on a multiple-case study which aims to investigate how novice university teachers construct professional identities as they process and utilize resources to promote professional development. Data were collected from 35 novice university teachers in China through prolonged individual interviews as a major source of data, with journal entries and other written protocols as a supplement. Data analysis reveals three types of resource-mediated identities, that is, resource collectors, resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Most importantly, policies direct value orientation with regard to what kinds of research are published and what kinds of journals are identified as offering significant knowledge contribution (Jeater 2018). This inevitably leads to inequalities, because university researchers who represent less institutionally valued scholarship are prone to being marginalised (Xu 2021). Such an institutional value orientation, as is imposed or even enforced, is often made operationally effective via policy documents such as journal rankings.…”
Section: Publishing As a Field Of Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, policies direct value orientation with regard to what kinds of research are published and what kinds of journals are identified as offering significant knowledge contribution (Jeater 2018). This inevitably leads to inequalities, because university researchers who represent less institutionally valued scholarship are prone to being marginalised (Xu 2021). Such an institutional value orientation, as is imposed or even enforced, is often made operationally effective via policy documents such as journal rankings.…”
Section: Publishing As a Field Of Actionsmentioning
confidence: 99%
“…Previous studies have examined how teacher-researchers agentically navigate contextual and personal factors to behave in certain ways in their professional practice (Hinostroza-Paredes 2021). For instance, Xu (2021) identifies the diverse manifestations of teacherresearchers' agency as they conceived and utilised professional resources in different ways in the work context. Similarly, Yuan (2021) reveals how teacher-researchers exercised agency in adapting their publishing practice as they responded to different university requirements.…”
Section: Agency As Manifested In the Fieldmentioning
confidence: 99%